2017
DOI: 10.1021/acsnano.6b07808
|View full text |Cite|
|
Sign up to set email alerts
|

Tuning Chemistry and Topography of Nanoengineered Surfaces to Manipulate Immune Response for Bone Regeneration Applications

Abstract: Osteoimmunomodulation has informed the importance of modulating a favorable osteoimmune environment for successful materials-mediated bone regeneration. Nanotopography is regarded as a valuable strategy for developing advanced bone materials, due to its positive effects on enhancing osteogenic differentiation. In addition to this direct effect on osteoblastic lineage cells, nanotopography also plays a vital role in regulating immune responses, which makes it possible to utilize its immunomodulatory properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
188
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 234 publications
(195 citation statements)
references
References 67 publications
(129 reference statements)
3
188
1
1
Order By: Relevance
“…Specifically, it was reported that cytokine‐ or drug‐loaded biomaterials can harness macrophage polarization and generate an osteogenic immune microenvironment. [[qv: 7b,16]] Moreover, some studies suggested that tuning the chemistry and topography of surfaces can manipulate the response of macrophages to biomaterials 17. In the present study, we investigated the osteoimmunomodulatory ability of the active ion zinc and its immunomodulatory and osteogenic effects on osteointegration.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Specifically, it was reported that cytokine‐ or drug‐loaded biomaterials can harness macrophage polarization and generate an osteogenic immune microenvironment. [[qv: 7b,16]] Moreover, some studies suggested that tuning the chemistry and topography of surfaces can manipulate the response of macrophages to biomaterials 17. In the present study, we investigated the osteoimmunomodulatory ability of the active ion zinc and its immunomodulatory and osteogenic effects on osteointegration.…”
Section: Discussionmentioning
confidence: 98%
“…Immunofluorescence staining and flow cytometry results validated the higher proportion of M2 macrophages on Zn‐coated SPEEK (Figure 4). As to the higher proportion of the M2 phenotype on SPEEK than on PEEK (Figure 4), reasons may be as follow: it is reported that porous structure can facilitate the attachment and spread of macrophages, then the physical and mechanical signals of porous surface can be translated into biological signals, and subsequently modulate local microenvironment and macrophage polarization 17, 28. As revealed in Figure 1A, porous structure with pore size about 0.5–1 µm can be observed on the surface of SPEEK, which may provide some biological signals for the polarization of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the main focus of many investigations has been their osteogenic potential, while their interaction with the immune system has often been overlooked. Chen et al have recently made a step forward toward unraveling the tight link between osteogenesis and immunology on ceramic substrates, mainly β‐TCP or porous alumina. However, the studies performed were limited to the evaluation of the effect of β‐TCP extracts rather than involving direct cell seeding on the material.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, effects of nanoroughness on osteoimmunity were also investigated. For example, the different size of gold nanoparticles (16–68 nm) on allylamine surface balanced secretion of cytokines in nanoroughness groups to enhance osteogenesis . Ma et al modified surface of TiO 2 with UV irradiation to give different roughness (6–12 nm).…”
Section: Biomaterials For Modulation Of Osteogenesismentioning
confidence: 99%